Hypertension is an independent risk factor for type 2 diabetes: the Korean genome and epidemiology study - Kim, Min-Ju (Hypertens Res, 2015)
Hypertension and diabetes share common risk factors and frequently co-occur. Although high blood pressure (BP) was reported as a significant predictor of type 2 diabetes, little is known about this association in Korea. This study investigated the relationship of prehypertension and hypertension with type 2 diabetes in 7150 middle-aged Koreans, as well as the effect of BP control on diabetes development over 8 years. At 8 years, 1049 (14.7%) of the 7150 participants had newly developed diabetes, including 11.2, 16.7 and 21.5% of baseline normotensive, prehypertensive and hypertensive subjects, respectively. The overall incidence rate of diabetes was 22.3 events per 1000 person-years. Subjects with baseline prehypertension (hazard ratio (HR), 1.27; 95% confidence interval (CI), 1.09–1.48) and hypertension (HR 1.51; 95% CI, 1.29–1.76) were at higher risk of diabetes than normotensive subjects after controlling for potential confounders (P-value for trend <0.001). These associations persisted even when subjects were stratified by baseline glucose status, sex and body mass index (BMI). The risk of diabetes was significantly higher in subjects who had normal BP at baseline and progressed to prehypertention or hypertension at 8 years (HR, 1.48; 95% CI, 1.20–1.83) than those with controlled BP, but these associations were not observed in subjects with baseline prehypertension and hypertension. These findings showed that prehypertension and hypertension are significantly associated with the development of diabetes, independent of baseline glucose status, sex and BMI. Active BP control reduced incident diabetes only in normotensive individuals, suggesting the need for early BP management.